2022
DOI: 10.1002/ddr.21911
|View full text |Cite
|
Sign up to set email alerts
|

Mitoquinone intravitreal injection ameliorates retinal ischemia–reperfusion injury in rats involvingSIRT1/Notch1/NADPHaxis

Abstract: Retinal ischemia–reperfusion injury (RIRI) is an important pathological process of many ocular diseases. Mitoquinone (MitoQ), a mitochondrial targeted antioxidant, is a potential compound for therapeutic development of RIRI. This study observed the effect of MitoQ on RIRI, and further explored its possible molecular mechanism. Temporary increase in intraocular pressure was used to establish rat model of RIRI to observe the effect of MitoQ treatment on retinal function, pathological injury, oxidative stress, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…MitoQ is one of the most widely studied mitochondria-targeted antioxidants, which can rapidly enter cells and accumulate in mitochondria, where it is converted into the active antioxidant panthenol form to participate in the antioxidant process [31]. Recent studies have confirmed that MitoQ plays an excellent protective role in ischemic diseases such as retinal ischemiareperfusion, renal transplantation, and intestinal ischemiareperfusion [32][33][34]. In the present study, we found that MitoQ significantly ameliorated renal dysfunction in I/R mice, which is consistent with an earlier study [18].…”
Section: Discussionmentioning
confidence: 99%
“…MitoQ is one of the most widely studied mitochondria-targeted antioxidants, which can rapidly enter cells and accumulate in mitochondria, where it is converted into the active antioxidant panthenol form to participate in the antioxidant process [31]. Recent studies have confirmed that MitoQ plays an excellent protective role in ischemic diseases such as retinal ischemiareperfusion, renal transplantation, and intestinal ischemiareperfusion [32][33][34]. In the present study, we found that MitoQ significantly ameliorated renal dysfunction in I/R mice, which is consistent with an earlier study [18].…”
Section: Discussionmentioning
confidence: 99%
“…2 Retinal IR injury (RIRI) is a major pathogenic mechanism of glaucoma, which is mostly unknown, containing neuroinflammation and neuronal death during pathological processes. 3 RIRI, a vital pathological process of multiple ocular diseases, 4 is a main reason for visual impairment or even blindness, and a useful and effective method to prevent visual decline needs to be further developed. 5 Inspired by that, we conducted this study to explore novel and efficient treatments.…”
Section: ■ Introductionmentioning
confidence: 99%